STATE OF LYSOSOMAL’ MEMBRANES OF RETINA AND VISUAL NERVE IS AT DEVELOPMENT OF EXPERIMENTAL GLAUCOMA - Сердюк В. Н. (World of Medicine and Biology, 2012)
Adult rabbits with experimental glaucoma were used in this study. We studied different forms of the lysosomal enzyme marker – acid phosphatase activity in the eye tissue during glaucoma process. Results suggest decrease activity of all ferments, compared to normal ranges.
Keywords: glaucoma; acid phosphatase; lysosomas